Rancang Bangun Sistem Kontrol Mixer Alginate Berbasis Arduino dan Nextion Display - Riky Hendra Lesmana; Izza Anshory; Indah Sulistiyowati; Jamaaluddin Jamaaluddin (Jurnal Otomasi Kontrol dan Instrumentasi, 2026)
This study aims to design and implement an Arduino-based alginate mixer control system with Nextion Display as the user interface. This system was developed to improve the accuracy of mixing time and maintain the consistency of mixing results in the production process. The method used is a design with an experimental approach through testing several variations of stirring time and comparison with a conventional manual timer-based system. The parameters observed include time error and viscosity values of the mixing results. The test results show that the Arduino-based system has better time accuracy with smaller and more stable error values. This has an impact on more consistent viscosity results, which values obtained are in the range of 100–110 dPa·s according to process standards. In addition, the developed system also provides ease of operation and monitoring through real-time displays on the Nextion Display. Thus, this system can be a more effective alternative compared to conventional systems in the alginate mixing process.